Caracterização temporal e espacial da temperatura do ar e da evapotranspiração de referência na Bolívia - Choque Conde, Esteban [UNESP] (2017)
The objective of this research was to study air temperature and reference evapotranspiration (ETo) in the different agroecological zones of Bolivia (Plains, Valleys and Andean) using statistical and geostatistical models, with air temperature database of 235 meteorological stations in Bolivia and 41 of neighboring countries was used. The study is presented in two chapters: The first describes the characterization of the values of the medium (Tmed) maximum (Tmax) and minimum (Tmin) air temperature, through three spatial distributions: Departments, hydrographic basins and agroecological zones. Being the latter the best alternative of analysis. Linear regression analysis allowed to obtain the estimation equations for Tmed, Tmax and Tmin in function of altitude, with high determination coefficients (R2). The deviations resulting from comparisons between the seasonal and monthly equations estimated values in relation to the annual average suggest, in most altitudes, seasonal or monthly equations use, mainly for Tmed and Tmin. Were presented the spatial variations Tmed, Tmax and Tmin through isothermal maps. The maps show the strong influence of altitude on temperature values, placing higher isotherms in the Plains zone (lowlands) and lower in the Andean zone (highlands). The second chapter describes the characterization of ETo in the three agroecological zones of Bolivia, using temperature as the input variable: McGuinness - Bordne, Hargreaves - Samani and Thornthwaite. All three methods show that altitude and latitude increases determine an ETo decrease, in the direction of the Plains zone to the Andean zone. The three methods linear regression analysis helped obtaining the ETo annual estimation equations in function of altitude, with McGuinness - Bordne model showing the best result, as its R2 was the highest. The deviations resulting from comparisons between equations of seasonal and monthly ETo values in relation to the annual values suggest, at most altitudes, seasonal or monthly equations use. The ETo spatial variations are presented through isoline maps, corroborate the strong influence of altitude in ETo values by placing isolines of higher values in the Plains zone, and of lower values in the Andean zone.